2011
DOI: 10.1164/rccm.201002-0232oc
|View full text |Cite
|
Sign up to set email alerts
|

Yin Yang 1 Is a Novel Regulator of Pulmonary Fibrosis

Abstract: Rationale: The differentiation of fibroblasts into myofibroblasts is a cardinal feature of idiopathic pulmonary fibrosis (IPF). The transcription factor Yin Yang 1 (YY1) plays a role in the proliferation and differentiation of diverse cell types, but its role in fibrotic lung diseases is not known. Objectives: To elucidate the mechanism by which YY1 regulates fibroblast differentiation and lung fibrosis. Methods: Lung fibroblasts were cultured with transforming growth factor (TGF)-b or tumor necrosis factor-a.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 47 publications
4
51
0
1
Order By: Relevance
“…Lin and colleagues demonstrated that the activity of transcription factor Yin Yang 1 (YY1) in fibroblasts promotes fibrogenesis by increasing myofibroblast differentiation and collagen production (46). YY1 is expressed at high levels in fibroblasts from lungs of patients with IPF and in mouse models of lung fibrosis.…”
Section: Fibroblasts and Matrixmentioning
confidence: 99%
“…Lin and colleagues demonstrated that the activity of transcription factor Yin Yang 1 (YY1) in fibroblasts promotes fibrogenesis by increasing myofibroblast differentiation and collagen production (46). YY1 is expressed at high levels in fibroblasts from lungs of patients with IPF and in mouse models of lung fibrosis.…”
Section: Fibroblasts and Matrixmentioning
confidence: 99%
“…As two major biomarkers of collagen, Hyp and α-SMA played important roles in deposition and remodeling of ECM. 27,28) Rg1 may exert anti-fibrosis effect through modifying deposition of collagen and ECM in IPF.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α–induced activation of YY1 represses Fas expression, indicating that YY1 contributes to TNF-α–induced cell survival (Huerta-Yepez et al, 2006). YY1 expression is markedly increased in idiopathic pulmonary fibrosis and in mouse models of lung fibrosis (Lin et al, 2011). In the CNS, YY1 also plays a critical role in regulating development and function and accordingly, its involvement in neurological diseases has been suggested (He and Casaccia-Bonnefil 2008).…”
Section: Discussionmentioning
confidence: 99%